Legumes crop rotation can improve food and nutrition security in Nepal (Agronomy Journal of Nepal, 2013)
An intensive review of the literatures was made to access the importance of crop rotation for sustainable agriculture in Nepal. Result shows that an appropriate crop sequences improves soil fertility, reduces fertilizer cost, controls soil erosion, makes environment healthy, increases crop yields and develop sustainable crop production in the long run. Based on the study, identification of location specific crop sequences, their extension and evaluation of the impact on food production are recommended. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 123-127 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9014